Reindeer warble fly larvae found in red deer
Seven third instar larvae of the reindeer warble fly (Hypoderma (=Oedemagena) tarandi) were found in a 2-3 year old male red deer Cervus elaphus) shot on 14 November 1985 at Todalen, western Norway. This it, the first report of H. tarandi from red deer. In reindeer third instar larvae are found from February to June, and the unusual date of this record indicates a delayed development of the larvae due to abnormal host reactions. Warble fly larvae, probably H. tarandi, are also reported from moose Alces alces) in northern Norway., number=1, journal=Rangifer, author=Nilssen, A. C. and Gjershaug, J. O., year=1988, month=Jun., pages=35–37